Motivation Of Bali Cattle Farmers Tinanggea and Palangga Subdistrict South Konawe Regency - Munadi, Laode; Harapin Hafid; La Ode Muh Munadi; Deki Zulkarnain; Sitti Rahma Ratu Pujian (Publisher Cv. Inara, 2021)
Tinanggea and Palangga subdistricts of South Konawe Regency have many cattle farmers and relatively more populations than other livestock. The research aims to find out the motivation of farmers in raising bali cattle in Tinanggea and Palangga subdistricts in June - July 2020. Sub-districts and villages were determined by purposive sampling based on the largest number of livestock, while respondents selected as many as 60 farmers in simple random sampling. Furthermore, the data obtained is analyzed using The Likert scale and explained derpively. The results showed a strong reason farmers keep Balinese cattle because of economic motivation (68.8%), entertainment motivation (56%), environmental motivation (36%), and (4) social status motivation (22%).